2013
DOI: 10.1542/peds.2012-3320
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Saturation Nomogram in Newborns Screened for Critical Congenital Heart Disease

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Universal oxygen saturation screening by pulse oximetry is now recommended for early detection of critical congenital heart disease. The distribution of saturations in asymptomatic newborns in a large population has not been described. WHAT THIS STUDY ADDS:Our study is the largest to date to establish simultaneous pre-and postductal oxygen saturation nomograms in asymptomatic newborns at ∼24 hours after birth. The mean postductal saturation is higher than preductal during this tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
3
15
0
1
Order By: Relevance
“…We therefore share, with caution, the concept that some authors have suggested: this method could become a standardised, objective measure in addition to the already established objective and subjective means to assess the clinical condition of a neonate. We consider that, thus far, studies of PI have proven that it could be an extremely valuable tool for the assessment of newborns’ health condition and that the future application of PI in neonatal intensive care is broad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore share, with caution, the concept that some authors have suggested: this method could become a standardised, objective measure in addition to the already established objective and subjective means to assess the clinical condition of a neonate. We consider that, thus far, studies of PI have proven that it could be an extremely valuable tool for the assessment of newborns’ health condition and that the future application of PI in neonatal intensive care is broad.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, in the neonatal population, most of the studies are focused in establishing parameters for the diagnosis and/or early detection of life-threatening conditions (9,11,15,18,22,25).…”
Section: Studies Of the Perfusion Index In Infantsmentioning
confidence: 99%
“…Studies in the neonatal population have highlighted the potential for PI to be used as an assessment tool in various aspects of an infant's health [6]. In particular, studies have associated PI in the newborn period with subclinical chorioamnionitis [7], as a possible screening tool for the presence of congenital heart malformations [8,9], as a predictor of low superior vena cava flow [10], and as a sign of improved tissue …”
Section: Introductionmentioning
confidence: 99%
“…A child who has not passed the screening by the third testing is considered to have failed. Most states and hospital systems adopted this protocol, and many have reported their experiences to date, including Minnesota, 15, 16 Washington, 17 California, 18 Arkansas, 19 Wisconsin, 20 Maryland, 21 and Vermont. 22 …”
Section: Screening Algorithmmentioning
confidence: 99%
“…Nurseries in Minnesota and California found a number of procedural inconsistencies due to misinterpretation of the AAP algorithm by the screening staff. 15, 18 These studies highlight the need for rigorous training of the screening staff and simplification of the protocol. Other research has suggested that the use of computer-based tools or apps can help to decrease the rate of misinterpretations.…”
Section: Screening Algorithmmentioning
confidence: 99%